2017
DOI: 10.1016/j.ajme.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRP-1 and GST-Pi in MDR and their inhibition by indomethacin in AML

Abstract: Background: MDR continues to be a major challenge to effective chemotherapeutic interventions against cancer. Defining major factor contributing to MDR and inhibiting their action may thus be used for reversing MDR. Aim: This work aimed to evaluate the role played by MRP-1 and GST-Pi in MDR, and to explore the possible role of indomethacin as an inhibitor of chemotherapy resistance in patients with AML. Subjects and methods: The study included 2 groups, one included 20 healthy volunteers and the second include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Maria Paprocka1 et al also reported overexpression (86%) of MRP 1 in patients who didn't reach remission (7). Though, some other studies showed that MRP 1 had no signi cance to anticipate treatment response, has no prognostic value, and its relationship with remission is somehow contentious (25)(26)(27)(28)(29). On the other hand, Antonella Maria Salvia, et al noticed upregulation of ABCC1/ MRP1 in relapsed and no remission groups.…”
Section: Discussionmentioning
confidence: 97%
“…Maria Paprocka1 et al also reported overexpression (86%) of MRP 1 in patients who didn't reach remission (7). Though, some other studies showed that MRP 1 had no signi cance to anticipate treatment response, has no prognostic value, and its relationship with remission is somehow contentious (25)(26)(27)(28)(29). On the other hand, Antonella Maria Salvia, et al noticed upregulation of ABCC1/ MRP1 in relapsed and no remission groups.…”
Section: Discussionmentioning
confidence: 97%